Editorial - Pacheco Romero, José (2015)
Two scientific impact have news in recent weeks. The first concerns the genetic correlations with human disease (1). The identification of a genetic correlation between features and complex human diseases can become a useful insight to help etiological prioritize a likely causal relationship. Until now it had not been able to establish this relationship because the information complete genotype of a particular individual was not known and there is extensive overlap of the sample in the meta-analysis. But now it has used a regression technique score LD crossing features that only requires a statistical summary of the study of association in the complete genome (genome-wide association study - GWAS) and has no bias overlay sample. With this method, researchers have come to estimate genetic correlations between 25 300 features a total of more than 1.5 million measurements of unique phenotypes, having found genetic correlations between anorexia nervosa and schizophrenia / BMI and educational attainment with various diseases. The results show the power of whole genome analysis, because until now had not found single nucleotide polymorphisms (SNPs) that were associated with anorexia nervosa and only three SNP for educational attainment (2).